MUMTAZ SMART Application for Improving Learning Quality at Muhammadiyah 1 Taman: Aplikasi MUMTAZ SMART untuk Meningkatkan Kualitas Pembelajaran di Muhammadiyah 1 Taman - Mucholladun , Wildan; Fariyatul , Eni (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The integration of technology in education is essential to achieve high-quality learning and ensure engaging, effective teaching practices. Specific background: Muhammadiyah schools, as part of Islamic-based education, face challenges in sustaining learning quality, particularly after the pandemic period when digital tools were widely adopted. Knowledge gap: While previous studies focused on the temporary role of digital platforms during emergency remote teaching, little is known about the long-term sustainability of MUMTAZ SMART in elementary school contexts. Aims: This study investigates how the MUMTAZ SMART application supports teaching and learning processes at Muhammadiyah 1 Taman Elementary School. Results: Findings reveal that the application strengthens instructional planning, online interaction, digital resource access, and evaluation, although challenges remain in teacher readiness, digital literacy, and infrastructure. Novelty: Unlike earlier research, this study highlights the continuous use of MUMTAZ SMART beyond the pandemic as a structured quality improvement tool. Implications: The results suggest that MUMTAZ SMART can serve as a model for other Muhammadiyah schools to institutionalize digital-based quality learning management.Highlights: Supports sustainable digital learning quality Identifies challenges in teacher and infrastructure readiness Offers a replicable model for Muhammadiyah schools Keywords: MUMTAZ SMART, Digital Education, Muhammadiyah School, Learning Quality, Educational Innovation